LITERASI KEUANGAN DIGITAL: MENANGKAL JERATAN PINJAMAN ONLINE - I Made Sudiksa; I Nyoman Sunarta; Gusi Putu Lestara Permana; I Made Suidarma; Ketut Elly Sutrisni; Ni Kadek Ayu Trisnadewi; I Gede K. Ananta Yoga (Sewagati, 2025)
The rapid development of digital technology has led to the emergence of financial technology lending (fintech lending), including online loan services that offer convenience and accessibility. However, these conveniences often come with hidden risks, particularly for individuals with low financial literacy. This community service program was conducted in Sumerta Village, East Denpasar, Bali, aiming to increase public awareness and understanding of personal financial management and the dangers of illegal online loans. The program implemented an interactive educational approach through public seminars, direct discussions, and the use of printed and digital media such as posters and stickers. The activities successfully raised community awareness regarding how to identify legal and illegal loan platforms and how to manage personal finances more responsibly. The initiative also empowered local residents to become financial literacy advocates within their communities. Overall, this program demonstrates the importance of strengthening digital financial literacy at the grassroots level to protect communities from predatory lending practices and to build sustainable financial behavior.